REPRESENTASI NILAI PENDIDIKAN KARAKTER DALAM FILM BUYA HAMKA & SITI RAHAM VOL. 2 - Aisah Fitri Nasution; Wahyu Ningsih; Hijrah Purnama Sari (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This research analyses the character education values in Buya Hamka & Siti Raham Vol. 2 using Kohlberg moral development theory. The focus is on the values of religiosity, honesty, cooperation, responsibility, and patriotism. This descriptive qualitative research uses primary data from dialogue and actions in the film, as well as secondary data from related articles and journals, which are collected through observation, recording, and document analysis. Descriptive analysis techniques were used to analyse the collected data. The steps of data analysis consisted of categorisation, interpretation, and presentation of findings. The results showed that Buya Hamka reflected post-conventional morals with universal ethical principles, while Siti Raham reflected moral standards through social compliance. The film is effective as an educational medium for moral values for the younger generation in the digital era.